REFLECTION PAPERS FOR COMMUNITY SERVICE LEARNING - Grove, Kathleen (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Reflection Paper #1 Due: Question #1:Prepare a 2 page report describing a program or highlighting an individual at your service learning site. In this report, identify the program, describe projects, leadership, include a brief description of the history of the organization. Should activities like this be expanded? What rewards accrue to the community? To those involved as providers?Question #2:The helping relationship is generally thought of as positive. What are some of the negative aspects? (1 page)Reflection Paper #2 Due: How does your service learning project provide insight into either social epidemiology or the meaning and experience of illness?